Answer:
[tex](f\circ g)(x)=\frac{1}{x^{2}}+\frac{8}{x}+12[/tex]
Step-by-step explanation:
Given that [tex]f (x) = x^{2}+6x+5[/tex] and [tex]g(x)=\frac{1}{x}+1[/tex] are the functions.
To find [tex](f\circ g)(x)[/tex] with the given two functions. ie., to find the composite function of f(x) and g(x) which is denoted by [tex](f\circ g)(x)[/tex]
[tex](f\circ g)(x)=f(g(x))[/tex]
[tex]=f(\frac{1}{x}+1)[/tex]
[tex]=({\frac{1}{x}+1})^{2}+6\times ({\frac{1}{x}+1})+5[/tex]
[tex] =\frac{1}{x^{2}}+\frac{2}{x}+1+\frac{6}{x}+6+5[/tex]
[tex]=\frac{1}{x^{2}}+\frac{8}{x}+12[/tex]
Therefore [tex](f\circ g)(x)=\frac{1}{x^{2}}+\frac{8}{x}+12[/tex]
Therefore the composite function of f(x) and g(x) is [tex](f\circ g)(x)=\frac{1}{x^{2}}+\frac{8}{x}+12[/tex]